Semantic description of cloud service agreements - Greenwell, Richard; Liu, Xiaodong; Chalmers, Kevin (Institute of Electrical and Electronics Engineers, 2015)
To provide cloud services as a utility there must be a mechanism for comprehensively and precisely specifying cloud service agreements to reduce differences in service perception between customers and suppliers. This paper proposes a description logic driven approach to specifying cloud service agreements as ontology, which allows agreement and negotiation between the parties in the service agreement. A unique contribution is provided by modelling of cloud service agreements as ontology which is precise and comprehensive. Future work sees the approach expanded to include a greater number of cloud service agreement artifacts and a service agreement specification for a financial calculation service.
Keywords: 004 Data processing & computer science; QA75 Electronic computers. Computer science; Utility; cloud computing; semantic description